An Early Detection of Latent Infection of Ralstonia solanacearum on Potato Tubers - Baharuddin Baharuddin; Tutik Kuswinanti; Ach Syaifuddin (Hasanuddin University, 2014)
Ralstonia solanacearum is not only a soil-borne pathogen but also a seedborne bacterial pathogen. National Seed Agency require that seed-source (G0) must free from bacterial wilt infection (0%) in potato seed certification process. This study aimed to determine an early and accurately detection of Ralstonia solanacearum in potato seedsource production (G0) on aeroponics cultivation system, which previously treated with microbial antagonists and artificialy infected with Ralstonia solanacearum. Seed potatoes were obtained from the previous study. Antagonist isolates NS01, S04, G06, and NG02 were applied separately in aeroponic system in nutrient solution, then artificially infected with R. solanacearum. These four isolates is quite effective inhibite R. solanacearum infection in potato aeroponic system with the intensity attach of 5, 7, 9 and 21% respectively, compared to 100% in control. Although the symptoms of wilt disease were appeared in plants, but the seeds did not show typical symptoms. In the positive control that inoculated with R. solanacearum without antagonists, revealing immediately wilt and death of plants, 14 days after inoculation. The result of polymerace chain reaction (PCR) using OLI1 and Y2 primers on tubers without antagonist with 100% disease incidence showed, that all of the tuber have positive results indicated by the appearance of DNA bands in the size of 287 bp. From visually healthy seeds sample resulted from antagonist treatment, only few of them have positive result and mostly other tubers showed negative result. This means that the role of antagonists on suppression of wilt disease, cannot totally guarantee the tubers free from latent infection of R. solanacearum.